2018
DOI: 10.18632/aging.101725
|View full text |Cite
|
Sign up to set email alerts
|

ΔNp63 promotes IGF1 signalling through IRS1 in squamous cell carcinoma

Abstract: Accumulating evidence has proved that deregulation of ΔNp63 expression plays an oncogenic role in head and neck squamous cell carcinomas (HNSCCs). Besides p63, the type 1-insulin-like growth factor (IGF) signalling pathway has been implicated in HNSCC development and progression. Most insulin/IGF1 signalling converges intracellularly onto the protein adaptor insulin receptor substrate-1 (IRS-1) that transmits signals from the receptor to downstream effectors, including the PI3K/AKT and the MAPK kinase pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 94 publications
0
11
1
2
Order By: Relevance
“…Accordingly, we showed that during keratinocyte differentiation there was a depression of the glucose metabolism (Figure 3C,D). Moreover, ΔNp63 is able to control the insulin receptor substrate (IRS) IRS1 [36], and in our p63RNAi experiments, it also controls IRS4 (Table S1, last row), both of which are responsible of the re-localization of GLUT4 transporter [37] on the plasma membrane, explaining the mechanism of glucose uptake impairment observed during differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we showed that during keratinocyte differentiation there was a depression of the glucose metabolism (Figure 3C,D). Moreover, ΔNp63 is able to control the insulin receptor substrate (IRS) IRS1 [36], and in our p63RNAi experiments, it also controls IRS4 (Table S1, last row), both of which are responsible of the re-localization of GLUT4 transporter [37] on the plasma membrane, explaining the mechanism of glucose uptake impairment observed during differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The IRS family includes four isoforms, IRS1-4 (Al-Salam and Irwin 2017;Machado-Neto et al 2018). IRS1 is a mediator of insulin and IGF1, both of which can bind to INSR (Simpson et al 2017;Frezza et al 2018). The PI3K/protein kinase B (also known as Akt) signalling pathway is mediated by IRS2 and plays an important role in cell growth, proliferation, and apoptosis (Lei et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylated INSR and IGF1R activate common substrates for downstream effector networks, including IRS, phosphatidylinositol 3-kinase (PI3K), and mitogen-activated protein kinase pathways (Frezza et al. 2018 ). Insulin and IGF1 bind and phosphorylate INSR and IGF1R, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Гормони молока можуть мати негативний вплив на здоров'я споживачів. Зокрема занепокоєння викликає ряд публікацій (Rogers et al, 2006;Duarte-Salles et al, 2014;Frezza et al, 2018;Rieunier et al, 2019), котрі пов'язують виникнення онкологічних захворювань зі споживанням молока та молочних продуктів. Пояснюється це наявністю у молоці низки гормонів, зокрема інсуліноподібного фактору росту, пролактину, простагландинів, глюкокортикоїдів, естрогенів та інших гормонів (Malekinejad & Rezabakhsh, 2015).…”
Section: вступunclassified